Anyoni v magnetu Kitaeva - Pleško, Erik (Matrika, 2019)
The article is about anyons - quasiparticles that Kitaev suggested in 2006 in his two dimensional model of a magnet. The reason why those particles are interesting is described in the introduction. Follows a section about quasiparticles in general. The majority of the article focuses on anyons in Kitaev's magnet and experimental evidence for their existence.
Keywords: anyoni; anyons; Kitaev magnet; kvazidelci; magnet Kitaeva; quasiparticles